Edging stiffness of ski touring bindings - Graf, S.; Litzenberger, S.; Sabo, A. (Procedia Engineering, 2011)
In this study ski touring bindings of the seasons 2009/10/11 are measured and compared concerning their edging stiffness. Additionally, the influence of different parameters; rubber boot sole, a touring boot, deflection of the ski and weight on the stiffness of the bindings were assessed. Ten different bindings of five brands were chosen to be measured with three ski setups with different fixations (fixed, hovering, bent ski) and with three different soles/boots, each with and without weight. As results, the travelled distance to a defined reaction force and back, the area enclosed by the hysteresis as well as an area/distance relation were calculated. The results concerning the sole influence showed a significant influence of averaged 54% more travelled distance, 94% bigger areas and therefore 17% higher area/distance relations. Furthermore additional weight showed a contrary effect on the different systems. In average the distance was 12% lower, whereas the areas got 12% larger, thus the area/distance relation was 27% higher. Ski deflection and the standard touring boot had a construction related, therefore very different, effect on the stiffness. It can be concluded that the bindings reacted differently to the changed parameters due to varying constructional parameters.